Interactions between char and tar during the steam gasification in a fluidized bed reactor. (15th July 2018) - Morin, Mathieu; Nitsch, Xavier; Hémati, Mehrdji
Highlights: Study on interactions between char and toluene at 850 °C in a fluidized bed reactor. Effect of steam and toluene partial pressure and solid media (olivine, sand, char). The toluene is polymerized on the char surface to produce coke and H2 . Char catalytic activity is dependent on the steam partial pressure in the reactor. The produced coke is much less reactive towards steam gasification than the char. Abstract: The aim of the present work is to understand the different interactions which may occur between the char and a tar model (toluene) in a fluidized bed reactor during biomass char gasification with steam. Experiments are conducted at 850 °C and atmospheric pressure with sand particles as solid medium. The influence of steam and toluene partial pressures on both the char reactivity and the presence of tar in the product gas was investigated in the range of 0.05–0.4 bars and 0.0025 and 0.0075 bars (10.1 and 30.4 g.Nm −3 ), respectively. Results showed that the presence of char in the fluidized bed reactor leads to toluene polymerization (cokefaction) which produces a carbonaceous deposit (coke) on its surface. This deposit is much less reactive towards steam gasification than the initial char. For the operating conditions used in this study, it was found that the rate of tars polymerization ( R p ) is always smaller than the one of coke and char gasification ( R sr + R g ). Finally, a comparison between the different solid catalysts in the fluidized bed reactor revealed that olivine is the best catalyst towards toluene conversion when the ratio P H 2 / P H 2 O is higher than 1.5 in the reactive gas atmosphere. Otherwise, for a steam partial pressure higher than 0.2 bars, "olivine + 3% char" and "sand + 3% char" were found to be the best compromise to limit the amount of tar in the product gas.